Implant failure after externally magnetic-controlled nail lengthening. Issue 11 (November 2021) - Rentenberger, Colleen; Haider, Thomas; Zak, Lukas; Wozasek, Gerald E.
Highlights: A large number of implant failures was observed; this has to be considered during patient selection and patient's education. No obvious risk factor e.g. previous surgeries, comorbidities and age was identified. In cases of slow bone healing, early revision surgery with an exchange to a solid trauma nail has to be considered to prevent nail breakage. Further improvement of the implant is required, given the costs of intramedullary limb lengthening in relation to the number of complications. Abstract: The number of intramedullary procedures to treat leg length discrepancy (LLD) has risen in the past decade and this has led to increased complications such as nail breakage. The aim of this study was to reveal our experience with implant failure after externally magnetic-controlled telescopic bone lengthening. We observed nail-breakage in 4 out of 24 patients (16.7%) after 6 to 15 months (median 13.5 months) following lower limb lengthening for LLD due to non-union or insufficient bone healing. Three femora and one tibia were treated in one posttraumatic and three congenital cases. Three out of the four patients had an elevated Charleston Comorbidity Index (CCI). Revision surgery involved removal of the broken nail and implantation of a trauma nail. At final follow-up all patients showed subjective satisfaction, achievement of desired lengthening with complete bone healing. Based on our results no unequivocal risk factor including number of previous surgeries, comorbidities and age was identified. In cases of delayed bone formation, early revision surgery with an exchange to a trauma nail has to be considered to prevent breakage of the intramedullary telescopic device.